Peran Komunikasi Kelompok dalam Membangun Hubungan yang Harmonis antar Volunteer Greenpeace Indonesia - Indah Octavianakesuma; Davis Roganda Parlindungan (UNIVERSITAS KALBIS, 2022)
Building harmony in an organization is very important for a large organization like Greenpeace, because to make a big event one of its success is good communication with their team. Because Greenpeace very often interacts with volunteers they even open up opportunities if the community wants to join in this environmental-related organization. This study discusses the role of group communication in building harmonious relationships within volunteer groups. The purpose of this study was to determine the role of group communication in building harmonious relationships among Greenpeace Indonesia volunteers. This research method uses a qualitative approach with descriptive research type. The results of this study indicate that the role of groups in effective communication can build harmonious relationships within the group as well as members who play an active role in building communication to maintain harmony within the Greenpeace Indonesia group of organizations. Communication development is carried out by making Line Communication in every activity that takes place as well as providing information in the Whatsapp group. Researcher's suggestion related to this research is to create a closer and more harmonious relationship, communication can also be done by adding activities between staff and volunteers